PENGARUH PENERAPAN MODEL PEMBELAJARAN PEMECAHAN MASALAH BERORIENTASI MASALAH MATEMATIKA TERBUKA TERHADAP HASIL BELAJAR DITINJAU DARI KETERAMPILAN METAKOGNITIF - I Komang Sukendra (Emasains : Jurnal Edukasi Matematika dan Sains, 2016)
This rescareh was an experimental research that was a 2 x 2 factorial design that involved the learning model as the free variable, the students match achievent as the bound variable and the metacognitive skill as the moderate variable. Recognise has all the variable can be tightly controlled so that this research could be classified as a pseudo research. All the hypo thesis examination had using Microsoft excel program and SISS No. for windows program. This research populations was the students of XI grade of SMA N 7 Denpasar in the academic year 2015/2016. The single was taken random from class XI science 1 and XI scince 2. Based on the data analys is it was discovered them on the first hypothesis. Examination of + test. Score is = 2,688 with of = 82 and the “Sig (2 tailed) score or p-value = 0,009. This was proved by the Fhitung = 9,49 and Ftable score is = 4,08 on 5% significans, because Fhitung > Ftable means Ho was rejected. It means the math learning achievement of the students those followed the implementation of the problem solving learning model of open math problem got better result. The those who followed the problem solving learning model. The second hypothesis examination of t-test showed t-score is = 3,433 of is 22, so the sig score (2-tailed) on p-value is = 0,002 smaller than the level alfa of 0,025 it also showed through tukey is 2,021. Qhitung is 3,35 is hile Qtable is 2,021. Qhitung > Qtabel Which means ho was rejected and H1 was acceptd. It means the students achivenent who followed the implementation of the problem solving learning model of open math problem got better score, compared with the students achievent who followed problem solving learning model toward the students who had low metacognitive score of t-test and t-score is = 4,012, of = 22 so than sig score (2-viled) or p-value is 0,002 smaller than alva level 0,025 . This was should Qhitung > Qtable that means Ho was rejected and H1 was accepted. It means the students math achieverment who followed problem oriented got better result solving learning model toward the students who had the metacognitif skill on the forth hypothesis the result of the accumulasiy of analysis varians (Anara) on the 2 lines showed that the FA score is 9,46 bigger that 4,08 (significant), means Ho was rejected and H1 . FAB = 34 smaller than 4,08. Ftabel score on dk A = 1, dkdalam = 44, = 0,05 in the score of 4,08, that because FABhitung < Ftabel (dk A = 1, dkdalam = 0,05) means that the Ho was acepted and H1 was rejected. That’s means there was no interaction between the implementation of learning solving problem which achieved with open math problem orientation and the students metacognitif skill who result of math learning.